Leiomyomatosis peritonealis disseminata: A case report and meticulous review of the literature. - Psathas, Giannos; Zarokosta, Maria; Zoulamoglou, Menelaos; Chrysikos, Dimosthenis; Thivaios, Ioannis; Kaklamanos, Ioannis; Birbas, Konstantinos; Mariolis-Sapsakos, Theodoros (Int J Surg Case Rep, 2017)
INTRODUCTION: Leiomyomatosis peritonealis disseminata (LPD) is a peculiar benign clinical disorder characterized by proliferation of peritoneal and subperitoneal nodules. LPD is a difficultly diagnosed benign disease that rarely degenerates into malignancy. PRESENTATION OF CASE: A 40-year-old Caucasian female with vaginal bleeding proceeded to our institution for elective excision of abdominal and pelvic masses which were firstly considered as leiomyosarcomas. The histologic diagnosis of the mass lesions revealed smooth muscle benign cells. This is the first case of LPD reported in Greece. A meticulous review of the literature was conducted as well. DISCUSSION: The differential diagnosis of LPD is difficult due to its clinical resemblance with peritoneal carcinomatosis or metastatic lesions and with benign metastasizing leiomyoma (BML) as well. Etiological factors, pathophysiology and clinical manifestations which lead to a safe diagnosis of LPD are adequately described. CONCLUSION: Surgeons' thorough knowledge concerning this rare clinical condition is fundamental and crucial in order to establish a correct diagnosis and assert the appropriate treatment and the minimization of the probability of malignant transformation of LPD.